Literature Review : Faktor-Faktor Yang Mempengaruhi Anemia Pada Ibu Hamil - Wahyu Ernawati; Dwi Andarwati; Allania Hanung; Reffy Dhamayanti (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Globally the prevalence of anemia in pregnant women worldwide is 40%. The prevalence of anemia in pregnant women in Indonesia in 2018 increased by 48.9% compared to 2013 of 37.1% of pregnant women with anemia. Anemia is a major health problem. pregnant women who experience anemia can experience complications during childbirth, LBW and morbidity in mother and baby. The purpose of the literature review is to review the factors that influence anemia in pregnant women from various research results. The research used the literature review method. The database used for this research journal is from the Pubmed Central (PMC)/Pubmed, Science Direct, and Google Scholar databases. using the keywords